CHILD EDUCATION IN PRESCHOOL PEDAGOGY (Conference Zone, 2022)
Pedagogy is an education at the center of comprehensive education of a person. Pedagogical education fulfills the demands of society. it is based on physical materialism, scientific philosophy, and is an objective reflection of things and their conditions. This article discusses about child’s education in preschool pedagogy.